2010
DOI: 10.2528/pier10012004
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Extension in a One-Dimensional Ternary Metal-Dielectric Photonic Crystal

Abstract: Abstract-Comparing with an all-dielectric binary photonic crystal, we show, in this work, that the photonic band gap in ternary metaldielectric photonic crystal can be significantly enlarged. First, the band gap enlargement due to the addition of the metallic film is examined in the case of normal incidence. Next, in the oblique incidence, a wider omnidirectional band gap can be obtained in such a ternary metal-dielectric photonic crystal. All the theoretical analyses are made based on the transfer matrix meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…The broadband characteristic is similar to that of the doublebarrier tunneling system, which is generally made of periodic photonic crystals [20][21][22][23][24][25][26]. If the double-barrier system is composed by two opaque barriers (R → 1), the first part in (5) part dominates the total group delay.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The broadband characteristic is similar to that of the doublebarrier tunneling system, which is generally made of periodic photonic crystals [20][21][22][23][24][25][26]. If the double-barrier system is composed by two opaque barriers (R → 1), the first part in (5) part dominates the total group delay.…”
Section: Resultsmentioning
confidence: 83%
“…Such phenomenon called superluminality is generally attributed to steep anomalous dispersion [1][2][3][4][5][6][7][8] and tunneling effect [9][10][11][12][13][14][15][16][17], which have been experimentally demonstrated in the electromagneticallyinduced-absorption [1][2][3][4][5]/ring-resonator [6][7][8] optical systems and the photonic/waveguide [9][10][11][12][13][14][15][16][17] systems, respectively. However, the systems employing the anomalous dispersion usually operate near the steep absorption line, which leads to a narrow superluminal frequency range as well as low transmission (for passive systems), while the systems associated with the tunneling mechanism also suffer from extremely low transmission [16][17][18][19][20][21][22][23][24][25][26]. Therefore, finding a new mechanism that supports both relat...…”
Section: Introductionmentioning
confidence: 99%
“…Periodic media like one-dimensional (1D) photonic band gap structures (PBGs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] have attracted great interest of researchers due to their remarkably useful capabilities to guide and control light propagation. In these 1D PBG structures, generally, two or more different optical materials are periodically arranged.…”
Section: Introductionmentioning
confidence: 99%
“…The approach is simple; this ternary structure can be fabricated by depositing a thin layer of a third material between the two layers of the binary structure periodically. However, this sandwiching of a thin layer of a third material between every two layers binary PBG structure periodically has remarkable consequences i.e., it drastically enhances the performance of 1D binary PBG structure to guide and control light propagation [10][11][12][13][14][15]. Recently, in a research work [15], it was found that the incidence angle based spectrum tuning capability of 1D binary PBG structure enhances when the structure is modified to 1D ternary PBG structure by sandwiching a thin layer of third material, between every two layers, constituting a period of lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Some methods to enlarge the frequency range of OBGs have been proposed, such as increasing the contrast of dielectric functions between the PC composites [3,4], using a chirped PC [20] or photonic heterostructure [21][22][23], or introducing the disorder into the periodic structures [24,25], etc. In recent years, one-dimensional ternary photonic crystals (1DTPCs) are also put forward to obtain the extended OBGs [10,[26][27][28][29][30][31]. 1DTPCs are constituted by three material layers in a period of the lattice.…”
Section: Introductionmentioning
confidence: 99%